1995
DOI: 10.1038/nm1195-1148
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of ex vivo gene therapy for homozygous familial hypercholesterolaemia

Abstract: The outcome of the first pilot study of liver-directed gene therapy is reported here. Five patients with homozygous familial hypercholesterolaemia (FH) ranging in age from 7 to 41 years were enrolled; each patient tolerated the procedure well without significant complications. Transgene expression was detected in a limited number of hepatocytes of liver tissue harvested four months after gene transfer from all five patients. Significant and prolonged reductions in low density lipoprotein (LDL) cholesterol were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
268
1
12

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 503 publications
(284 citation statements)
references
References 21 publications
3
268
1
12
Order By: Relevance
“…These patients had a long-term 6-20% reduction of LDL cholesterol levels and importantly, reconstituted in vivo LDL catabolism. 65 However, no therapeutic benefit was obtained in any patients due to the modest decrease in LDL cholesterol. Therefore, this clinical trial demonstrated the feasibility and safety of ex vivo approach but also its therapeutic inefficacy in treating metabolic liver diseases.…”
Section: Mulv Retroviral Vectorsmentioning
confidence: 93%
See 2 more Smart Citations
“…These patients had a long-term 6-20% reduction of LDL cholesterol levels and importantly, reconstituted in vivo LDL catabolism. 65 However, no therapeutic benefit was obtained in any patients due to the modest decrease in LDL cholesterol. Therefore, this clinical trial demonstrated the feasibility and safety of ex vivo approach but also its therapeutic inefficacy in treating metabolic liver diseases.…”
Section: Mulv Retroviral Vectorsmentioning
confidence: 93%
“…Consequently, two-thirds of the isolated hepatocytes were lost during ex vivo cell manipulations and transplanted hepatocytes only represented o1% of patient liver mass. 61,65 In addition, cells were also damaged by trypsin treatment, which negatively affected their engraftment and survival ability. Finally, efficacy of ex vivo gene therapy is hampered by cell transplantation because only a limited number of hepatocytes (corresponding to 5% of patient liver mass) can be safely transplanted at one time, and that engraftment and liverrepopulating ability of transplanted hepatocytes is low.…”
Section: Mulv Retroviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The ability to cryopreserve isolated hepatocytes for immediate availability and to transplant cells from a single donor to multiple recipients makes this modality attractive. Additionally, HT is metabolically less stressful than liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Providing selective growth advantage to transplanted hepatocytes could markedly enhance the efficacy of HT. Therefore, we and others are investigating strategies for massively repopulating the host liver by preferential mitotic stimulation of the engrafted hepatocytes.…”
Section: Introductionmentioning
confidence: 99%